EXPERIMENTAL AND NUMERICAL ANALYSIS OF FLOW OVER A PICKUP TRUCK - Ince, Ibrahim Timucin; Mercan, Hatice; Onur, Nevzat (BEGELL HOUSE INC, 2021)
The drag forces and the overall drag coefficient of a typical pickup truck are investigated experimentally and the 3D numerical analysis is performed. A detailed 1/4-scale model is constructed and experiments are performed at Reynolds numbers around 2 x 10(6) in the Ankara Wind Tunnel (ART). The experimental study is divided into two stages: in the first stage the pressure distribution along the symmetry axis is measured and in the second stage the drag forces and overall drag coefficient are measured at five different wind speeds. The measured data are compared with the 3D numerical simulation performed in FLUENT. The turbulence standard, realizable, and RNG k-epsilon models, the standard and SST k-omega models, and finally the RSM are compared for three near-wall treatments: standard wall function, nonequilibrium wall function, and enhanced wall function. The comparison revealed that for lower velocities the best turbulence model-wall treatment couple is the realizable k-epsilon model with Reynolds stress model with standard wall function, whereas for higher velocities the standard k-epsilon turbulence model is observed to be more compatible with experimental data. The highest pressure value is measured in front of the pickup truck and the lowest pressure value is evaluated at the rim where the windshield and the roof meet.
Keywords: pickup trucks; pressure measurement; flow visualization; drag coefficient; CFD; turbulence models; and Reynolds wall stress treatments; AERODYNAMICS; DRAG; Thermodynamics